2022
DOI: 10.1002/anie.202213268
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Synthesis of One‐Dimensional Covalent Organic Frameworks with 4‐c sql Topology for Enhanced Fluorescence Emission

Abstract: Covalent organic frameworks (COFs) have been extensively investigated due to their unique structure, porosity, and functionality. However, at the topological level, COFs remain as two‐dimensional (2D) or three‐dimensional (3D) structures, while COFs with one‐dimensional (1D) topology have not been systematically explored. In this work, we proposed a synthetic strategy for the construction of 1D‐COFs based on non‐linear edges and suitable high‐symmetry vertices. Compared with their 2D‐COFs counterparts, the 1D‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…More recently, Chen et al. demonstrated that 1D COFs based on nonlinear edges show enhanced fluorescence [6c] . Nevertheless, 1D COFs are still rare, and developing more 1D COFs to extend the family of COFs has been underexplored.…”
Section: Figurementioning
confidence: 99%
“…More recently, Chen et al. demonstrated that 1D COFs based on nonlinear edges show enhanced fluorescence [6c] . Nevertheless, 1D COFs are still rare, and developing more 1D COFs to extend the family of COFs has been underexplored.…”
Section: Figurementioning
confidence: 99%
“…[24] Up to now, 1D COFs still very rare and only few examples are reported. [25][26][27][28] Boron-dipyrromethene (BODIPY) dyes are one of the most versatile fluorophores with excellent visible-light absorption ability, thermal and photochemical stabilities, high fluorescence quantum yields, and chemical robustness. [29,30] These photophysical and chemical properties of BODIPY attracted tremendous attentions and they can be widely used in photocatalysis, bioimaging, sensing and luminescent devices.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extremely high anisotropy and the entropy‐driven random packing of organic chains, the synthesis of 1D COFs are filled with huge challenge [24] . Up to now, 1D COFs still very rare and only few examples are reported [25–28] …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] To date, many Au-, Ag-, and Cu-based nanostructured materials, metal-organic frameworks, and single-atom catalysts have been developed to apply in the CO 2 electroreduction reaction (CO 2 RR). [16][17][18][19][20][21][22] However, the CO 2 RR generally faces challenges in achieving high selectivity and a high current density due to the intrinsic thermodynamic stability of CO 2 and the competitive hydrogen evolution reaction (HER), hindering its practical application. Therefore, the development of highly efficient electrode materials that can overcome these problems is desirable.…”
Section: Introductionmentioning
confidence: 99%